2011
DOI: 10.5152/jtgga.2011.69
|View full text |Cite
|
Sign up to set email alerts
|

HPV DNA and Pap smear test results in cases with and without cervical pathology

Abstract: Objective:The aim of the study was to determine the HPV prevalance and its relation to Pap smear, colposcopy and colposcopy directed biopsy in our region of Eskisehir, Turkey. Material and Methods:A total of 615 women who applied to the outpatient clinic between December 2009 and December 2010 constituted our study population. All patients underwent pelvic examination and Pap smear sampling. Patients who had pathological cervical appearance or Pap smear results of ASCUS, AGUS, LSIL or HSIL were referred to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…But, the rates of the present study were much lower than the ones reported for Western populations, in general (de Sanjose et al, 2003;Duggan et al, 2006;Kroupis et al, 2007;Kulig et al, 2010;Marques et al, 2011). However, our results were very similar to those reported from other Islamic countries like Saudi Arabia, Egypt, and Iran (Jamal et al, 2003;elAll et al, 2007;Nokiani et al, 2008) that may be ascribed to low prevalence of HPV (Tuncer et al, 2006;Ozalp et al, 2012), religion, or the conservative cultures, akin to Turkish population. Besides, the mentioned rates detected by cervical screening may also vary with the nature of populations screened.…”
Section: Discussionsupporting
confidence: 91%
“…But, the rates of the present study were much lower than the ones reported for Western populations, in general (de Sanjose et al, 2003;Duggan et al, 2006;Kroupis et al, 2007;Kulig et al, 2010;Marques et al, 2011). However, our results were very similar to those reported from other Islamic countries like Saudi Arabia, Egypt, and Iran (Jamal et al, 2003;elAll et al, 2007;Nokiani et al, 2008) that may be ascribed to low prevalence of HPV (Tuncer et al, 2006;Ozalp et al, 2012), religion, or the conservative cultures, akin to Turkish population. Besides, the mentioned rates detected by cervical screening may also vary with the nature of populations screened.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, this study demonstrated that HPV infection only occurs in a relatively small number of OSCC cases. In the literature, the rate of HPV positivity in HNSCC is provided with a wide range and often substantially differs between from one study to another [32, 33]. Further examination of published data shows that the wide range of HPV+ status in SCC is the result of poor differentiation between OSCC and OPSCC [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis including 576.281 patients from 120 studies HPV prevalence was found 32.1% worldwide [11]. In Turkey, the prevalence of HPV was found between 2.1 to 38.9% in different studies [12][13][14][15][16][17]. The HPV infection rate in patients with abnormal cytology is higher.…”
Section: Discussionmentioning
confidence: 97%
“…Table 4 summarizes the recent studies with available full-text from Turkey investigating the relationship between HPV status and abnormal cytological results. The previous studies from Turkey reported the rate of HPV infection among patients with abnormal cervical cytology between 12% and 80% [13][14][15][16][17][18][19][20][21][22][23][24][25]. This wide range probably originated from the detection method used.…”
Section: Discussionmentioning
confidence: 99%